(untitled) (CAHIERS MAGELLANES-NS, 2024)
Positive health outcomes are linked to patient experience (PE), which is a crucial component of the standard of medical care. PE is challenging in the pediatric emergency department (PED) because of the necessity to balance the requirements of the patient and their family while they are being treated. According to a survey given to patients and their families after their visit to the PED, we found a chance to enhance our PE. Method : We put together a diverse team, created our goals, and assessed the procedure using quality improvement techniques. To monitor our performance, we used run charts and a main driver diagram. The group also kept an eye on a number of crucial subcategories within our process of progress. Over the course of nine months, we sought to raise our overall PE score from 86.1 to 89.7 in order to meet institutional goals. Results: We increased our overall PE score from 86.1 to 89.8 over a 6-month period. In a similar vein, all of our relevant subscores—physician performance, patient activities in the waiting area, radiology wait times, staff sensitivity, and delay communication—saw increases. A cross-departmental committee, staff training, team meetings, and rounds in the waiting and exam areas were among the interventions. Every metric showed consistent progress. Conclusions: Measurable PE improvement may be achieved even in this complicated environment through the meticulous and rigorous process evaluation and improvement efforts of a multidisciplinary team.